Developing an Integrated Surveillance Interface - Andersson, Lars (My University, 2011)
This report goes through the design that was created and implemented to produce the foundation for a modern, fast and reliable surveillance interface that builds on the existing total security system OnGuard from the company Lenel. The solution is divided into two programs, a server application which handles the communication with the OnGuard system and other third party programs that the program should be able to communicate with, and a client application which the user uses to interact with the server. The server application is developed using C# and is compiled to run under the .NET virtual machine. The client application is developed in C++ using the Qt and Qt Quick framework and can be compiled to run under many different operating systems. This project was never intended to, nor does it, deliver any finished product but more so investigates the possibilities of building a surveillance interface that builds upon OnGuard and utilizes Qt Quick to produce a modern and fast user interface.
Keywords: Datavetenskap (datalogi); Computer Science